Aging aggravates ischemic stroke‐induced brain damage in mice with chronic peripheral infection. Issue 5 (7th July 2013) - Dhungana, Hiramani; Malm, Tarja; Denes, Adam; Valonen, Piia; Wojciechowski, Sara; Magga, Johanna; Savchenko, Ekaterina; Humphreys, Neil; Grencis, Richard; Rothwell, Nancy; Koistinaho, Jari
Summary Ischemic stroke is confounded by conditions such as atherosclerosis, diabetes, and infection, all of which alter peripheral inflammatory processes with concomitant impact on stroke outcome. The majority of the stroke patients are elderly, but the impact of interactions between aging and inflammation on stroke remains unknown. We thus investigated the influence of age on the outcome of stroke in animals predisposed to systemic chronic infection. Th1‐polarized chronic systemic infection was induced in 18–22 month and 4‐month‐old C57BL/6j mice by administration of Trichuris muris (gut parasite). One month after infection, mice underwent permanent middle cerebral artery occlusion and infarct size, brain gliosis, and brain and plasma cytokine profiles were analyzed. Chronic infection increased the infarct size in aged but not in young mice at 24 h. Aged, ischemic mice showed altered plasma and brain cytokine responses, while the lesion size correlated with plasma prestroke levels of RANTES. Moreover, the old, infected mice exhibited significantly increased neutrophil recruitment and upregulation of both plasma interleukin‐17α and tumor necrosis factor‐α levels. Neither age nor infection status alone or in combination altered the ischemia‐induced brain microgliosis. Our results show that chronic peripheral infection in aged animals renders the brain more vulnerable to ischemic insults, possibly by increasing the invasion of neutrophils and altering the inflammation status in the blood and brain. Understanding the interactions between age and infections is crucial for developing a better therapeutic regimen for ischemic stroke and when modeling it as a disease of the elderly.